2016
DOI: 10.1016/j.pmcj.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Modeling patterns of activities using activity curves

Abstract: Pervasive computing offers an unprecedented opportunity to unobtrusively monitor behavior and use the large amount of collected data to perform analysis of activity-based behavioral patterns. In this paper, we introduce the notion of an activity curve, which represents an abstraction of an individual’s normal daily routine based on automatically-recognized activities. We propose methods to detect changes in behavioral routines by comparing activity curves and use these changes to analyze the possibility of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…In the case of work by Dodge et al [80], by Hodges et al [81], by Dawadi et al [82], and by Lotfi et al [83], unexpected behavioral patterns are viewed as a health risk for individuals who are at risk of cognitive decline. These researchers have found that an increase in the number of activity anomalies and variation in behavior patterns such as activity times and walking speed are correlated with changes in cognitive health.…”
Section: Acting In Response To Threatsmentioning
confidence: 99%
“…In the case of work by Dodge et al [80], by Hodges et al [81], by Dawadi et al [82], and by Lotfi et al [83], unexpected behavioral patterns are viewed as a health risk for individuals who are at risk of cognitive decline. These researchers have found that an increase in the number of activity anomalies and variation in behavior patterns such as activity times and walking speed are correlated with changes in cognitive health.…”
Section: Acting In Response To Threatsmentioning
confidence: 99%
“…In regards to change detection approaches, a handful of studies have investigated change that can be detected in human behavior patterns. These approaches have quantified change statistically [ 12 , 13 , 14 ], graphically [ 13 , 15 , 16 ], and algorithmically [ 15 , 17 , 18 , 19 ]. Recently, Merilahti et al [ 12 ] extracted actigraphy-based features from data collected for at least one year.…”
Section: Related Workmentioning
confidence: 99%
“…The authors showed that combining mutual information based weighting of sensor events and adding past contextual information to the feature leads to better performance. To analyse possible changes in cognitive or physical health, Dawadi et al [42] introduced the notion of activity curve and proposed a permutation-based change detection in activity routine algorithm. The authors validated their approach with a two-year smart home sensor data.…”
Section: Related Workmentioning
confidence: 99%